Relationships between psychological resilience and competitive level in judo - Rodriguez-Romo, G.; Blanco-García, C.; Garrido-Muñoz, M.; García-Merino, S.; Acebes-Sánchez, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION Numerous researchers and professionals have been interested in the role of psychological resilience in competitive sports and its relationship with sports performance. In this sense, various studies confirm a positive relationship between high levels of resilience and optimal sports performance. Could resilience be a psychological quality among athletes who reach a high competitive level? The purpose of this study was to assess the possible association between the competitive level in Judo and psychological resilience, both in men and women.